Solar power's rise and promise - Ernesto M. Pernia; Maria Janela M. Generoso (University of the Philippines, School of Economics (UPSE), 2015)
Time was when solar energy was facilely dismissed as impractical, inefficient, and pricey. In recent years, however, innovations in technology, regulation, and financing have resulted in remarkable efficiency improvements and price reductions, thereby reversing the skepticism about this renewable energy (RE) source. In this paper, we explore how this has happened, to what extent photovoltaic solar technology has been accepted around the world, and what might be its potential for inclusive green growth. We find that adoption of both on-grid and off-grid solar systems has been widespread and rapidly increasing. Particularly noteworthy is the utilization of small- scale individual or distributed off-grid solar home systems (SHS) in remote and underserved areas in the developing world, including East Africa and South Asia. It appears that the Philippines has been a relative latecomer. Data show that solar power's "installed" capacity remains a tiny fraction of all RE sources (that also include hydro, geothermal, wind, biomass, and ocean). Moreover, such capacity is for ongrid only; there seems none as yet installed for off-grid SHS. We conclude with the paper's main points and possible implications for policy and research.
Keywords: O10; O14; Q20; Q28; 330; Renewable energy; Inclusive green growth; Rural electrification; Economic development